ความสัมพันธ์ระหว่างความฉลาดทางอารมณ์ของผู้บริหารสถานศึกษากับแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษากรุงเทพมหานคร - จิกจักร, หนึ่งฤทัย; ทองโปร่ง, อำนวย (วารสารวิชาการนวัตกรรมการบริหารการศึกษา, 2025)
Abstract The purpose of this research is (1)to study the emotional intelligence of school administrators under Bangkok Primary Educational Service Area Office, (2) to study the work motivation of teachers under Bangkok Primary Educational Service Area Office, and (3) to find the relationship between emotional intelligence of school administrators and the work motivation of teachers under Bangkok Primary Educational Service Area Office. This is a survey research. The sample group consisted of 285 teachers teaching in schools under Bangkok Primary Educational Service Area Office in the academic year 2024. The sample size was determined using the ready-made table of Cohen, Manion, and Morrison. The research instrument was a questionnaire. The sampling method used was multi-stage random sampling and simple random sampling. The statistics used in the research include included mean (𝑥̅), standard deviation (SD), and Pearson's Product-Moment Correlation Coefficient. The research results were found as follows; (1) The emotional intelligence of school administrators under Bangkok Primary Educational Service Area Office for overall is at the highest level, (2) The work motivation of teachers under Bangkok Primary Educational Service Area Office for overall and in each aspect is at the highest level and (3) The emotional intelligence of school administrators and the work motivation of teachers under Bangkok Primary Educational Service Area Office has the positive relationship at the high level with statistical significance at the .01 level. Keywords: Emotional intelligence; work motivation of teachers; school administrators